High-strength 95 aluminum oxide ceramic as well as preparation method and application thereof
By using boehmite and hydrotalc as the binder for alumina ceramics, the pores and cracks caused by the decomposition of the binder during sintering are solved, and alumina ceramic preparation with high strength and high density is achieved.
Patent Information
- Application Number
- CN202411763073.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
During the preparation of existing alumina ceramics, some binders decompose and overflow during the sintering process, resulting in pores and cracks in the ceramics, reducing density, and affecting strength and hardness.
Boehmite and hydrotalc are used as the main components of the binder to obtain boehmite-hydrtalc composite sol through a specific preparation method, which is used in the preparation process of alumina ceramics.
It effectively avoids the problem of decomposing and overflowing of traditional binders under high temperature conditions, improves the density of alumina ceramics, and enhances its strength and hardness.
Smart Images

Figure CN119569427A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alumina ceramics, and in particular relates to a high-strength 95 alumina ceramic and a preparation method and application thereof. Background Art
[0002] 95% Alumina ceramic is a common technical ceramic material with high hardness, good wear resistance and excellent electrical insulation properties. It plays an important role in the fields of electronics, electricity, machinery, chemical industry, etc. Alumina ceramics are usually prepared by processes such as dry pressing, cold isostatic pressing, slurry casting and hot pressing. These processes can ensure the density and uniformity of ceramic materials, thereby improving their mechanical properties and service life. The strength of alumina ceramics is one of its most important mechanical properties, which is affected by many factors, including the preparation process of the material, grain size and structure, grain boundary characteristics and impurity content. In common molding processes, a binder component is required. The selection and use of the binder has a significant impact on the final performance of the product. The addition of the binder can improve the fluidity of the powder and facilitate automatic filling of the mold wall during molding, which is especially important for dry pressing. However, some of the binders used in the existing preparation process of alumina ceramics will decompose and overflow during the sintering process, resulting in pores and cracks in the alumina ceramics, resulting in a decrease in the density of the alumina ceramics, which in turn affects the alumina ceramics. Strength and hardness limit the application scope of alumina ceramics. The prior art CN117923887A discloses a production process for high-hardness alumina ceramics, which uses yttria-modified polyvinyl alcohol as an alumina ceramic binder. Compared with polyvinyl alcohol, its bonding performance is greatly improved. Adding it into the system as a binder can reduce the amount of binder used, thereby reducing the holes and cracks formed during the debinding process, and helping to improve the density during the sintering process; however, the amount of polyvinyl alcohol added in the prior art is relatively large, and yttria has limited improvement on the density and strength of alumina ceramics. Therefore, it is necessary to provide a preparation method for high-strength alumina ceramics. Summary of the invention
[0003] In order to solve the problems mentioned in the above background technology, the present invention provides a method for preparing high-strength 95 alumina ceramics. By using boehmite and hydrotalcite as the main components of the binder, a specific preparation method is adopted to obtain the binder of the present invention, which is used in the preparation process of alumina ceramics to obtain high-strength and high-density alumina ceramic materials.
[0004] One object of the present invention is to provide a high-strength 95% alumina ceramic, characterized in that it comprises the following components by mass percentage: 95% alumina, 0.5-2% sintering aid, and the remainder is a binder, wherein the binder is a boehmite-hydrotalcite composite sol.
[0005] Furthermore, the purity of the aluminum oxide is ≥99.99%, and D50=0.5 μm.
[0006] Furthermore, the sintering aid is one of titanium dioxide and manganese dioxide, and the particle size is 180-200nm.
[0007] Furthermore, the boehmite-hydrotalcite composite sol is prepared by the following method:
[0008] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:1-3, and ground to a particle size of 60-100 nm to obtain a nano powder mixture.
[0009] S2: adding the ground nano-powder mixture into a dispersant and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nano-powder mixture to the dispersant is 10:0.1-0.5.
[0010] S3: slowly adding a nitric acid solution with a pH value of 2-3 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5-1 mL:5 g, to obtain the binder of the present invention.
[0011] When HNO3 is added to the binder precursor, + Adsorbed on the particle surface, NO3 - The particles are rearranged in the liquid phase, forming a double electric layer on the surface of the particles. The existence of the double electric layer causes the particles to repel each other. When the repulsive force is greater than the attractive force, the aggregated particles disperse into small particles to form a sol.
[0012] Furthermore, in step S1, the particle size of boehmite and hydrotalcite before grinding is 180-200 nm.
[0013] Furthermore, the dispersant in step S2 is any one of ammonium polymethacrylate, polyvinyl alcohol and triammonium citrate.
[0014] Another object of the present invention is to provide a method for preparing high-strength 95% alumina ceramics, characterized in that it comprises the following steps:
[0015] 1) mixing and grinding alumina and a sintering aid to obtain a mixture;
[0016] 2) adding the mixture obtained in step 1) into the boehmite-hydrotalcite composite sol and mixing them evenly;
[0017] 3) The mixed material treated in step 2) is molded to obtain a green body, and then debinded and sintered to obtain an alumina ceramic.
[0018] Furthermore, the sintering temperature is 1280-1320°C.
[0019] Since the binder produces magnesia spinel and magnesium oxide during the high-temperature sintering process, it can significantly reduce the sintering temperature of alumina. When the sintering temperature is too high, it will cause abnormal grain growth, reduced porosity, and overburning. Therefore, the sintering temperature of the present invention is preferably 1280-1320°C.
[0020] Furthermore, the debinding heating rate is 3°C-5°C / min, and the debinding temperature is 350°C-580°C.
[0021] Another object of the present invention is to provide an application of high-strength 95 alumina ceramics in the field of ceramic substrates.
[0022] The present invention has the following beneficial effects:
[0023] The present invention adopts boehmite and hydrotalcite as the main components of the binder, and obtains the binder in combination with a specific preparation method. The binder is applied to the alumina ceramic preparation process, which can avoid the disadvantage that pores and cracks appear in the alumina ceramic due to the decomposition and overflow of the traditional binder under high temperature conditions, thereby improving the density of the alumina ceramic and improving the strength and hardness of the alumina ceramic.
[0024] The hydrotalcite component is used in the alumina ceramic binder of the present invention. During the alumina ceramic forming process, as the temperature rises, it gradually separates from the crystal water and carbon dioxide to form magnesium aluminum spinel and periclase. The magnesium aluminum spinel plays a pinning effect at the Al2O3 grain boundary, hindering the growth of Al2O3 grains, thereby refining the Al2O3 grains, reducing pores, and improving density. That is, magnesium aluminum spinel can refine the microstructure of alumina ceramics and improve density. The smaller the grains, the more grain boundaries, the greater the hindrance to dislocation movement, and the resistance to material deformation increases accordingly, so the hardness is higher; the higher the density, the lower the porosity, and the higher the hardness.
[0025] The MgO produced by calcining the hydrotalcite as the alumina ceramic binder of the present invention is due to the 2+ radius With Al 3+ radius Similar, during the sintering process, Mg 2+ Easy to replace Al in Al2O3 3+ , forming point defects, which will promote mass transfer during the sintering process of alumina, thereby increasing the growth rate and densification rate of alumina grains. MgO can change the anisotropic liquid-solid interface energy, thereby reducing the boundary free energy, so it can effectively inhibit the abnormal growth of grains and help to homogenize the ceramic structure.
[0026] The MgO produced by calcining the hydrotalcite in the binder of the present invention can significantly reduce the temperature of the conversion of boehmite and alumina to α-Al2O3 during the sintering process, thereby reducing the calcination temperature of the alumina ceramic. That is, the present invention can obtain a high-density alumina ceramic product by calcining at a relatively low temperature.
[0027] The binder used in the present invention acts as a binder in the early stage of the sintering process, thereby reducing the pores and cracks generated during the sintering process due to excessive use of organic binders. The magnesium aluminum spinel and magnesium oxide generated by hydrotalcite during the sintering process can act as a sintering aid, thereby reducing the amount of sintering aid added. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM spectrum of the alumina ceramic prepared in Example 2 of the present invention; DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.
[0030] It should be noted that the alumina ceramics in the following specific embodiments of the present invention are all prepared by the following method, the only difference being the specific type of sintering aid and the specific composition of the binder in different embodiments. Please refer to the corresponding specific embodiments for details, which will not be repeated here.
[0031] Alumina with a purity of ≥99.99%, D50=0.5μm and a sintering aid with a particle size of 180nm are prepared in a mass ratio of 92:10; the weighed raw materials are placed in a ball mill, and a planetary ball mill is used to maintain a speed of 550r / min for rapid ball milling and mixing for 1.5h, and the mixed slurry is dried at 120°C for 24 hours; an alumina ceramic precursor is obtained. The binder is taken in a mass ratio of alumina precursor: binder of 105:1, the alumina ceramic precursor is poured into a ceramic mortar, and then the binder is added, and after being fully mixed, it is placed in a sealed bag and sieved through a 40-mesh screen, and then placed in a steel mold of a hand-operated tablet press for pressing and sintering at a temperature of 1300°C.
[0032] Example 1
[0033] The invention discloses an alumina ceramic, which is composed of 95% alumina, 0.5% titanium dioxide and the remainder of boehmite-hydrotalcite composite sol.
[0034] The boehmite-hydrotalcite composite sol described in this embodiment is prepared by the following method:
[0035] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:2, and ground to a particle size of 80 nm to obtain a nanopowder mixture.
[0036] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:2.
[0037] S3: slowly adding a nitric acid solution with a pH value of 2.5 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0038] Example 2
[0039] An alumina ceramic is composed of 95% alumina, 1.5% titanium dioxide and the remainder of boehmite-hydrotalcite composite sol.
[0040] The boehmite-hydrotalcite composite sol described in this embodiment is prepared by the following method:
[0041] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:2, and ground to a particle size of 80 nm to obtain a nanopowder mixture.
[0042] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:2.
[0043] S3: slowly adding a nitric acid solution with a pH value of 2.5 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0044] Example 3
[0045] The invention discloses an alumina ceramic, which is composed of 95% alumina, 2% titanium dioxide and the balance of boehmite-hydrotalcite composite sol.
[0046] The boehmite-hydrotalcite composite sol described in this embodiment is prepared by the following method:
[0047] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:2, and ground to a particle size of 80 nm to obtain a nanopowder mixture.
[0048] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:2.
[0049] S3: slowly adding a nitric acid solution with a pH value of 2.5 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0050] Example 4
[0051] An alumina ceramic is composed of 95% alumina, 1.5% titanium dioxide and the remainder of boehmite-hydrotalcite composite sol.
[0052] The boehmite-hydrotalcite composite sol described in this embodiment is prepared by the following method:
[0053] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:1, and ground to a particle size of 80 nm to obtain a nanopowder mixture.
[0054] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:1.
[0055] S3: slowly adding a nitric acid solution with a pH value of 2 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5 mL:5 g, to obtain the binder of the present invention.
[0056] Example 5
[0057] An alumina ceramic is composed of 95% alumina, 1.5% titanium dioxide and the remainder of boehmite-hydrotalcite composite sol.
[0058] The boehmite-hydrotalcite composite sol described in this embodiment is prepared by the following method:
[0059] S1: Boehmite and hydrotalcite are mixed in a mass ratio of 1:3, and ground to a particle size of 100 nm to obtain a nanopowder mixture.
[0060] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:3.
[0061] S3: slowly adding a nitric acid solution with a pH value of 3 into the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 1 mL:5 g, to obtain the binder of the present invention.
[0062] Comparative Example 1
[0063] The invention discloses an alumina ceramic, which is composed of 95% alumina, 1.5% titanium dioxide and the balance of boehmite sol.
[0064] The boehmite sol described in this embodiment is prepared by the following method:
[0065] S1: Grind boehmite to a particle size of 80 nm to obtain a nanopowder mixture.
[0066] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:2.
[0067] S3: slowly adding a nitric acid solution with a pH value of 2.5 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0068] Comparative Example 2
[0069] An alumina ceramic is composed of 95% alumina, 1.5% titanium dioxide and the remainder hydrotalcite sol.
[0070] The hydrotalcite sol described in this embodiment is prepared by the following method:
[0071] S1: Grind the hydrotalcite to a particle size of 80 nm to obtain a nanopowder mixture.
[0072] S2: adding the ground nanopowder mixture into polyvinyl alcohol and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:2.
[0073] S3: slowly adding a nitric acid solution with a pH value of 2.5 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.8 mL:5 g, to obtain the binder of the present invention.
[0074] Performance Characterization of Alumina Ceramic Materials
[0075] The microstructure of alumina ceramic materials was analyzed by SEM scanning electron microscope, the specific model of which is JSM-6700F scanning electron microscope; a universal tensile testing machine was used to test the three-point bending strength of ceramics (sample size 3mm×4mm×35mm, 10 samples were measured in each group and the average value was taken); the fracture toughness test mainly adopted the single ring cantilever beam (SENB) test method, and the micro Vickers hardness test: the test standard is
[0076] GB / T16534-2009 Fine Ceramics Room Temperature Hardness Test Method, room temperature is about 20℃, use 40x objective lens, load is HV0.5 (4.903N), hold time is 10 seconds, some performances are shown in the following table:
[0077] Specific embodiments hardness Fracture toughness Bending strength Example 1 17.5±0.8GPa <![CDATA[6.65MPa.m 1 / 2 ]]> 338.45MPa Example 2 18.3±0.7GPa <![CDATA[6.88MPa.m 1 / 2 ]]> 346.33MPa Example 3 17.8±0.7GPa <![CDATA[6.34MPa.m 1 / 2 ]]> 336.89MPa Example 4 17.7±0.6GPa <![CDATA[6.55MPa.m 1 / 2 ]]> 337.88MPa Example 5 17.4±0.9GPa <![CDATA[6.26MPa.m 1 / 2 ]]> 335.69MPa Comparative Example 1 16.3±0.8GPa <![CDATA[5.92MPa.m 1 / 2 ]]> 316.35MPa Comparative Example 2 16.5±0.9GPa <![CDATA[6.01MPa.m 1 / 2 ]]> 325.87MPa
[0078] By comparing the above-mentioned relevant embodiments and comparative examples, it can be seen that the present invention adopts boehmite and hydrotalcite as the main components of the binder, and obtains the binder in combination with a specific preparation method. Applying it to the preparation process of alumina ceramics can avoid the disadvantage of pores and cracks in alumina ceramics due to decomposition and overflow of traditional binders under high temperature conditions, thereby improving the density of alumina ceramics and improving the strength and hardness of alumina ceramics.
[0079] The alumina ceramic binder of the present invention uses hydrotalcite as a component, and its structural formula is Mg6Al2(OH) 16 CO3.4H2O, which only loses interstitial water below 200℃. At around 273℃, brucite begins to dehydroxylate. At around 270-400℃, as dehydroxylation occurs, the sample loses more water and carbon dioxide at the same time; when calcined at around 1000℃, it transforms into MgAl2O4 and periclase.
[0080] During the alumina ceramic forming process, as the temperature rises, hydrotalcite gradually detaches from crystal water and carbon dioxide to form magnesium aluminum spinel and periclase. Magnesium aluminum spinel plays a pinning effect at the Al2O3 grain boundary, hindering the growth of Al2O3 grains, thereby refining Al2O3 grains, reducing pores, and improving density. That is, magnesium aluminum spinel can refine the microstructure of alumina ceramics and improve density. The smaller the grains, the more grain boundaries, the greater the hindrance to dislocation movement, and the greater the resistance to material deformation, so the higher the hardness; the higher the density, the lower the porosity, and the higher the hardness.
[0081] The MgO produced by calcining the hydrotalcite as the alumina ceramic binder of the present invention is due to the 2+ radius With Al 3+ radius Similar, during the sintering process, Mg 2+ Easy to replace Al in Al2O3 3+ , forming point defects, which will promote mass transfer during the sintering process of alumina, thereby increasing the growth rate and densification rate of alumina grains. MgO can change the anisotropic liquid-solid interface energy, thereby reducing the boundary free energy, so it can effectively inhibit the abnormal growth of grains and help to homogenize the ceramic structure.
[0082] When heated, boehmite first loses physically adsorbed water, and as the temperature rises, it starts to lose chemically adsorbed water from 210°C, and gradually undergoes a dehydroxylation reaction after 310°C. At 1200°C, the sample transforms into rhombohedral α-Al2O3. The present invention selects boehmite as a binder, which can stabilize the slurry in the early stage, and after pyrolysis, it is a single α-Al2O3, that is, it is converted into α-Al2O3 in situ, without any impurities introduced into the system.
[0083] The MgO produced by calcining the hydrotalcite in the binder of the present invention can significantly reduce the temperature of the conversion of boehmite and alumina to α-Al2O3 during the sintering process, thereby reducing the calcination temperature of the alumina ceramic. That is, the present invention can obtain a high-density alumina ceramic product by calcining at a relatively low temperature.
[0084] The binder used in the present invention acts as a binder in the early stage of the sintering process, thereby reducing the pores and cracks generated during the sintering process due to excessive use of organic binders. The magnesium aluminum spinel and magnesium oxide generated by hydrotalcite during the sintering process can act as a sintering aid, thereby reducing the amount of sintering aid added.
Claims
1. A high strength 95 alumina ceramic, characterized in that The invention comprises the following components by mass percentage: 95% of alumina, 0.5-2% of sintering aid, and the balance of a binder, wherein the binder is a boehmite-hydrotalcite composite sol.
2. A high strength 95 alumina ceramic as claimed in claim 1, characterized in that: The purity of the aluminum oxide is ≥99.99%, and D50=0.5 μm.
3. A high strength 95 alumina ceramic as claimed in claim 1, characterized in that: The sintering aid is one of titanium dioxide and manganese dioxide, and the particle size is 180-200nm.
4. A high strength 95 alumina ceramic as claimed in claim 1, characterized in that: The boehmite-hydrotalcite composite sol is prepared by the following method: S1: mixing boehmite and hydrotalcite in a mass ratio of 1:1-3, and grinding to a particle size of 60-100 nm to obtain a nanopowder mixture; S2: adding the ground nanopowder mixture to the dispersant and mixing them evenly to obtain a binder precursor, wherein the mass ratio of the nanopowder mixture to the dispersant is 10:0.1-0.5; S3: slowly adding a nitric acid solution with a pH value of 2-3 to the binder precursor, wherein the solid-liquid ratio of the binder precursor to the nitric acid solution is 0.5-1 mL:5 g, to obtain the binder of the present invention.
5. A high strength 95 alumina ceramic as claimed in claim 4, characterized in that: In step S1, the particle size of boehmite and hydrotalcite before grinding is 180-200 nm.
6. A high strength 95 alumina ceramic as claimed in claim 4, characterized in that: The dispersant in step S2 is any one of ammonium polymethacrylate, polyvinyl alcohol and triammonium citrate.
7. A method for preparing the high-strength 95 alumina ceramic according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: 1) mixing and grinding alumina and a sintering aid to obtain a mixture; 2) adding the mixture obtained in step 1) into the boehmite-hydrotalcite composite sol and mixing them evenly; 3) The mixed material treated in step 2) is molded to obtain a green body, and then debinded and sintered to obtain an alumina ceramic.
8. A method for preparing the high-strength 95 alumina ceramic according to any one of claims 1 to 6 according to claim 7, characterized in that: The sintering temperature is 1280-1320°C.
9. A method for preparing the high-strength 95 alumina ceramic according to any one of claims 1 to 6 according to claim 7, characterized in that: The debinding heating rate is 3°C-5°C / min, and the debinding temperature is 350°C-580°C.
10. Application of the high-strength 95% alumina ceramic according to any one of claims 1 to 6 in the field of ceramic substrates.
Citation Information
Patent Citations
Production process of high-hardness aluminum oxide ceramic
CN117923887A